A regiospecific co-assembly method to functionalize ordered mesoporous metal oxides with customizable noble metal nanocrystals - Li, Jichun (2025)
An efficient regiospecific co-assembly (RSCA) strategy is developed for general synthesis of mesoporous metal oxides with pore walls precisely decorated by highly dispersed noble metal nanocrystals with customized parameters (diameter and composition). It features the rational utilization of the specific interactions between hydrophilic molecular precursors, hydrophobic noble metal nanocrystals, and amphiphilic block copolymers, to achieve regiospecific co-assembly as confirmed by molecular dynamics simulations. Through this RSCA strategy, we achieved a controllable synthesis of a variety of functional mesoporous metal oxide composites (e.g., WO3, ZrO2, TiO2) with in-pore walls precisely decorated by various noble metal nanocrystals of tailored components (Au, Ag, Pt, Pd and their nanoalloys) and sizes (3.0-8.5 nm). As an example, the obtained mesoporous 0.5-Ag/WO3 material has a highly interconnected mesoporous structure and uniform 6.5 nm Ag nanocrystals confined in the mesopores, showing superior NO sensing performances with high sensitivity, good selectivity, and stability at low working temperature (127 °C). In situ spectroscopy study indicates that the NO sensing process involves a unique gas-solid reaction, where NO molecules are converted into chemisorbed NO x species over the sensitive materials, inducing a remarkable change of resistance and outputting a dramatic response signal.